Highly uniform and polarization-independent Y-branch with mode filter based on deeply etched silica-on-silicon waveguide. (April 2019) - Jiang, Weifeng
Highlights: Mode filter can suppress high-order modes and achieve a uniform splitting-ratio. More compact mode filter is found compared to the reported silica-waveguide based ones. Polarization-independent Y-branch is based on deeply etched silica-on-silicon waveguide. Ultra-low nonlinearity over the O + E + S + C + L band can be measured for the Y-branch. Abstract: A slight misalignment between an optical fiber and a Y-branch would excite high-order modes and subsequently induce a snaking behavior of the input light, which would dramatically deteriorate the device performance. Here, a highly uniform and polarization-independent Y-branch based on deeply etched silica-on-silicon (SoS) waveguide is proposed, optimized, fabricated, and characterized, in which a mode filter with the quadratic-spline boundary is inserted to suppress the high-order modes. The proposed Y-branch is optimized by using three-dimensional full-vectorial finite difference beam propagation method. The experimental results show that the proposed Y-branch is with an ultra-low nonlinearity over a broad bandwidth from 1250 nm to 1620 nm, a low polarization dependent loss of less than 0.2 dB, and an ultra-low relative power difference of less than 0.04.